BOVINE MASTITIS CAUSED BY Candida Spp.: REPORT OF THREE CASES NOT RESPONDING TO ANTIBACTERIAL AGENTS (Journal of Veterinary Medicine and Animal Production, 2022)
The present study investigated the causative agents among 34 non responsive bovine mastitic cases for routine antibacterial agents (neomycin, cefaloxin, penicillin). Milk samples were collected cultured for fungi and isolated organisms were identified using standard mycological procedures. Three of the 34 cows (8.8%) revealed yeasts growth. The yeasts were identified as Candida rugosa (two isolates) and Candida tartarivorans. The study concluded that Candida species represent a significant role (8.8%) among not responding to antibacterial treatment dairy cows. Such unresponsive cases should be considered for regular routine fungal culture regularly in order to initiate specific antifungal treatment before udder become completely damaged.